ANALISIS PEMAHAMAN PERATURAN PEMERINTAH NOMOR 23 TENTANG PAJAK PENGHASILAN PADA UMKM BEKASI - Achmad Dany; Priyastiwi Priyastiwi (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2023)
This study aims to determine the level of understanding and describe the implementation of Government Regulation No. 23 of 2018 on UMKM in Bekasi. The method used in this research is quantitative, and the data source is primary data. By using the Slovin formula to obtain a sample and using a questionnaire to collect data. The data analysis method used is the analysis of the results with a Likert scale. The results showed that 43% of respondents strongly agreed with the statement of Taxpayer Compliance, 37% of respondents stated strongly agree with the statement of the application of PP. 23 of 2018, and 34% of respondents disagreed with the Self Assessment System statement. It can be interpreted that UMKM actors in Bekasi are aware of and understand taxpayer compliance, and the implementation of final tax provisions and fines if they do not pay taxes, UMKM actors know and agree, but there are still those who do not agree. There are weaknesses in the Self Assessment System, the lack of awareness of UMKM actors in recording or accounting in calculating the amount of turnover.